Acute inflammation promotes early cellular stimulation of the epithelial and stromal compartments of the rat prostate - Quintar, Amado Alfredo (2010)
Acute inflammation promotes early cellular stimulation of the epithelial and stromal compartments of the rat prostate Amado A. Quintar1, Andreas Doll2, Carolina Leimgruber1, Claudia M. Palmeri1, Felix D. Roth1, Mariana Maccioni3, Cristina A. Maldonado1* 1Center of Electron Microscopy, School of Medical Sciences, National University of Cordoba, Córdoba, Argentina 2Biomedical Research Unit, Research Institute Vall d´Hebron University Hospital, Barcelona, Spain 3CIBICI-CONICET, Department of Clinical Biochemistry, School of Chemical Sciences, National University of Cordoba, Córdoba, Argentina email: Cristina A. Maldonado (cmaldon@cmefcm.uncor.edu) *Correspondence to Cristina A. Maldonado, Facultad de Ciencias Médicas, Centro de Microscopía Electrónica, Universidad Nacional de Córdoba, Pab. Biología Celular 1° piso, Haya de La Torre esq. Enrique Barros, Ciudad Universitaria, X5000HRA Córdoba, Argentina. The authors of this manuscript have nothing to declare. Funded by: Consejo Nacional de Investigaciones Científicas y Técnicas (CONICET) FONCyT-ANPCyT (PICT grant) KEYWORDS prostate inflammation ? bacterial infection ? cell stimulation ? proliferation ? smooth muscle cells ABSTRACT BACKGROUND It has been proposed that prostatic inflammation plays a pivotal role in the pathophysiology of benign hyperplasia and prostate cancer. However, little information is available about the prostatic reaction to bacterial compounds in vivo. Our aim was therefore to evaluate the early effects of bacterial infection on rat ventral prostate compartments. METHODS Using a rat model of acute bacterial prostatitis by Escherichia coli, we analyzed the histological and ultrastructural changes in the prostate at 24, 48, and 72 hr postinfection. Prostatic tissues were immunostained for prostatic binding protein (PBP), ACTA2, ErbB1, and ErbB2 receptors, TUNEL, and markers of cell proliferation. Dot and Western blots for PBP, ACTA2, ErbB1, ErbB2, and TGF1 were also performed. RESULTS The prostatic epithelium became hypertrophied, with increases in PBP and ErbB1 expression at 24 hr postinfection. Moreover, inflammation induced the expression of ErbB2, a receptor strongly involved in carcinogenesis. These alterations were more pronounced at 48 hr, but the epithelium also showed apoptosis and finally atrophy at 72 hr postinfection, with a decrease in PBP and ErbB receptors. Interestingly, the epithelial cells exhibited a high level of proliferation in response to the bacteria. The stromal reaction to acute inflammation was initially characterized by smooth muscle hypertrophy. Afterwards, muscle cells acquired a secretory phenotype, with a reduction in ACTA2 at 72 hr postinfection. CONCLUSIONS Prostatic inflammation, even at the early stages, promotes atrophic and proliferative changes, and the upregulation of ErbB receptors together with dedifferentiation of smooth muscle cells. These data suggest that repetitive reinfections could lead to uncontrolled growth in the prostate gland.